Evaluación del complejo enzimático celulasa en hongos nativos del Perú - Llacza Ladera, Henry Frans (2021)
In Peru, information on the biotechnological potential of native fungi for the degradation of cellulose presents few records. This work aimed to evaluate the cellulolytic activity of isolated fungi in the departments of Cajamarca, Lima, Junín and Huánuco. 289 species of fungi were subjected to reactivation after a conservation period of 7 years using filter paper and Czapeck broth, evaluated semi-quantitatively using the radial diffusion technique on Czapeck Na-CMC agar to then select five strains that were morphologically identified and its cellulolytic capacity was also determined by the Somogyi-Nelson method. 90% (260) of the fungi that underwent semi-quantitative evaluation were reactivated, selecting five strains for their greater clearance area: 14.9, 12.5, 12.0, 14.4 and 12.7 x 102 mm2; SA 726 (Paecilomyces sp), SA 668 (Paecilomyces sp), SA 651 (Paecilomyces sp), SA 683 (Fusarium sp) and HN 566 (Aspergillus sp) with EA of: 0.048, 0.042, 0.042, 0.080 and 0.048 IU / ml respectively. The native strains evaluated maintain good viability over time and retain the ability to degrade cellulose. These strains can be used in biotechnological processes for the treatment of agroindustrial effluents.